Play on : now, then & Fleetwood Mac, the autobiography - Fleetwood, Mick; Bozza, Anthony (Little, Brown and Company, 2014)
Mick Fleetwood has been a member of the ever-evolving Fleetwood Mac, one of the world's most successful and adored bands, for over four decades. Here he tells the full and candid story of his life as one of music's greatest drummers and bandleaders, the cofounder of the deeply loved supergroup that bears his name and that of his bandmate and lifelong friend John McVie. Play On sheds new light on Fleetwood Mac's raucous history, describing the highs and lows of being in the band that Fleetwood was determined to keep together.--From publisher description.